Teach Aquaculture Curriculum: Dancing with Brine Shrimp - Elisa J. Livengood; Cortney L. Ohs; Amber L. Garr; R. Leroy Creswell; Carlos V. Martinez; Craig S. Kasper; Brian E. Myers; Frank A. Chapman (EDIS)
FA176, a 7-page activity by Elisa J. Livengood, Cortney L. Ohs, Amber L. Garr, R. Leroy Creswell, Carlos V. Martinez, Craig S. Kasper, Brian E. Myers, and Frank A. Chapman, is activity 14 of the Teach Aquaculture Curriculum. In this activity for grades 5-12, students will hatch and culture brine shrimp to observe the behavior and the different development stages of the organisms. Includes student performance standards. Published by the UF School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences, July 2010.